The Impact of Green Human Resource Management on Organizational Citizenship Behavior for the Environment (OCBE) - Warman, Cecep; Debataraja, Lorhenson; Febrianata, Eka; Kusumawati, Retno Ryani; Sucihati, Sucihati (Westscience Press, 2025)
This study investigates the impact of Green Human Resource Management (GHRM) practices on Organizational Citizenship Behavior for the Environment (OCBE) in Indonesia. Using a quantitative approach, data were collected from 130 employees across various industries through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS 3). Results show that GHRM significantly and positively influences OCBE, with an explained variance (R²) of 42%. Among the dimensions of GHRM, green training and green rewards emerged as the strongest predictors of OCBE, while green recruitment and green performance appraisal also demonstrated significant but slightly weaker effects. These findings highlight the strategic role of HRM in fostering voluntary pro-environmental behaviors among employees, particularly in the Indonesian cultural context where collectivist values support sustainability. The study contributes to the literature by validating the GHRM–OCBE relationship in a developing country and by identifying the relative importance of different HR practices. Practically, organizations are encouraged to design HR strategies that integrate sustainability into training, rewards, recruitment, and performance management systems to strengthen both environmental performance and employee engagement.